Impact of a child-to-child programme on knowledge, attitude and practices regarding tobacco hazards among government school children in urban Belagavi: an interventional study - Revagoud, Kalmeshwar; Reddy, Chelikam Veeraraghavendra; Patil, Darshan; Sarawade, Ravindra (International Journal Of Community Medicine And Public Health, 2025)
Background: Tobacco initiation commonly begins during adolescence, making school-based preventive strategies essential. Peer-led and participatory approaches such as the child-to-child (CtC) method may enhance awareness and influence behavioural change. This study assessed the impact of a CtC educational intervention on knowledge, attitudes, and practices regarding tobacco use among government school children in urban Belagavi. Methods: A pre- and post-test interventional study was conducted among 160 students from two government high schools. IX-standard students (trainers) were educated using structured sessions and subsequently trained VIII-standard students (trainees) following the CtC approach. A validated questionnaire assessed sociodemographic characteristics, knowledge, attitudes, and practices before and two months after the intervention. Wilcoxon signed rank test and Mann-Whitney U Test were used for analysis. Results: Knowledge improved significantly in both groups, with trainers and trainees attaining post-test median scores of 17, compared to 11 and 9 at baseline (p<0.05). Attitude scores also improved markedly (trainers: 6 to 8; trainees: 3 to 8; p<0.05). Favourable attitudes toward tobacco avoidance increased substantially. Ever-use and past 30-day tobacco use decreased in both groups, while attempts to discourage tobacco use among family members increased. Awareness of environmental risk cues-such as tobacco sale points and anti-tobacco posters-also improved post-intervention. Conclusions: The CtC approach effectively enhanced students’ knowledge, attitudes, and selected tobacco-related practices. Peer-led, child-centred strategies hold promise for strengthening school-based tobacco prevention initiatives and influencing family and environmental awareness.